The Role of Character Education in Improving the Quality of Islamic Education at Pondok Pesantren Salafiyah Al-Madinatul Munawwaroh - Wahyuni, Sri; Syoviana, Elvi; Andre, Lesis; Yunanda, B.R.E. (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study discusses the role of character education in enhancing the quality of Islamic education at Salafiyah Al-Madinatul Munawwaroh Islamic Boarding School. Character education is considered a crucial element in moral and spiritual development. The research uses a qualitative descriptive approach with observation, interviews, and documentation techniques. The results show that character education at the boarding school is implemented through the habituation of Islamic values, the enforcement of school rules, and routine religious activities. These strategies have proven effective in shaping students to be disciplined, responsible, honest, and respectful towards their teachers and peers.The research method employed a qualitative descriptive approach. The subjects of the study were students, caregivers, and teachers at Salafiyah Al-Madinatul Munawwaroh Islamic Boarding School. Data were collected through direct observation, in-depth interviews, and documentation. The purpose of this research was to comprehensively describe how character education is implemented at the boarding school and its influence on the students' personality quality. The collected data were analyzed qualitatively through data reduction, data presentation, and drawing conclusions. The study further reveals that character education is applied through various strategies, such as implementing regulations, fostering noble behavior, and applying educational sanctions for rule violations. The school leaders and teachers play an active role in guiding students to become disciplined, responsible individuals who respect others. The values instilled include discipline, honesty, responsibility, and proper etiquette toward teachers. These values are applied through classroom learning, religious activities, and daily life in the dormitory.